Charge Distribution Controls On‐Target Separation of Low Nucleophilicity Anions in Layered Double Hydroxides. Issue 31 (22nd September 2022) - Sudare, Tomohito; Tamura, Shuhei; Kashiwazaki, Maru; Nakamura, Yuki; Kawaguchi, Kenta; Shiiba, Hiromasa; Fujisawa, Kazunori; Tipplook, Mongkol; Tanaka, Hideki; Hayashi, Fumitaka; Teshima, Katsuya
Abstract: Host–guest chemistry principles and mechanisms have been exploited to separate harmful and valuable ionic species. However, separating low nucleophilicity anions using these protocols is difficult due to weak host–guest interactions. Herein, using layered double hydroxides (LDHs), it is demonstrated that guest–guest interactions considerably influence the separation of a low nucleophilicity nitrate. LDHs exhibit considerably low nitrate ion storage capacities due to the co‐precipitation synthesis method. Hence, a topochemical reaction is applied to control the cation arrangement in the LDHs. Structural analyses determine that a hexagonal cation arrangement is facilitated. Isotherm analysis reveals that the obtained LDHs improve the capacity up to 250% of that of typical less‐ordered LDHs. Finally, further isotherm analysis in combination with theoretical calculations, it is revealed that the hexagonal arrangement effectively facilitates a stable guest–guest interactions—hydrogen‐bond between the interlayer nitrate ions and water molecules, which contributes to high ion‐storage. Abstract : The underlying prerequisite for materials design to achieve on‐target separation of low nucleophilic anions has been unclear. Herein, by establishing the cation‐ordered LDHs via topochemical reaction, which is applied to separation of the nitrate ion, a stable guest–guest interaction is demonstrated—hydrogen‐bonding network between the nitrate ions, water molecules, and LDHs framework is critical for the highly efficient separation.